Review of plagiarism detection and control & copyri ghts in India - Prof. S.S.Karadage; Prof. Mahesh S. Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
Plagiarism software’s has been in use for almost a decadeto get the sense of “theft of intellectual property".However, in today’s digital world the easy access to the web, large databases, and telecommunication in general,has turned plagiarism into a serious problem for publishers, researchers and educational institutions. The first partof this paper discusses the different plagiarism detection techniques such as text based, citation based and shapebased and compared with respect of their features and performanceand an overview of different plagiarismdetection methods used for text documents have taken. The second halfof the paper is fully dedicated tocopyrights in India